Myocardial Disease and Long-Distance Space Travel: Solving the Radiation Problem - Meerman, Manon; Bracco Gartner, Tom C. L.; Buikema, Jan Willem; Wu, Sean M.; Siddiqi, Sailay; Bouten, Carlijn V. C.; Grande-Allen, K. Jane; Suyker, Willem J. L.; Hjortnaes, Jesper (Frontiers in Cardiovascular Medicine, 2021)
Radiation-induced cardiovascular disease is a well-known complication of radiation exposure. Over the last few years, planning for deep space missions has increased interest in the effects of space radiation on the cardiovascular system, as an increasing number of astronauts will be exposed to space radiation for longer periods of time. Research has shown that exposure to different types of particles found in space radiation can lead to the development of diverse cardiovascular disease via fibrotic myocardial remodeling, accelerated atherosclerosis and microvascular damage. Several underlying mechanisms for radiation-induced cardiovascular disease have been identified, but many aspects of the pathophysiology remain unclear. Existing pharmacological compounds have been evaluated to protect the cardiovascular system from space radiation-induced damage, but currently no radioprotective compounds have been approved. This review critically analyzes the effects of space radiation on the cardiovascular system, the underlying mechanisms and potential countermeasures to space radiation-induced cardiovascular disease.